Thomas Merton: a pilgrim in search of inner life - Ródenas, Elvira (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Thomas Merton after a dissipated life went through a change leading to him converting and becoming a cistercian monk. His life was an authentic pilgrimage in search of the inner life described in his writings. This paper aims to present a systematic synthesis of TM’s spirituality and inner life; it has been structured in six paragraphs and an appendix: 1. TM a monk for the entire world. 2. The human being, a creature for love: freedom and agony in search of the sense of life. 3. The inner life. 4. The encounter with God and our response. 5. Christian life and prayer: contemplation, the pinnacle of the spiritual life. The appendix is devoted to his very last days in Asia, describing his pilgrimage as well as his ecumenical dimension and aperture to the rest of religions. The paper addresses the following topics: the characteristics of the modern human being: love, freedom and agony, sin, pain and happiness, identity and holiness; Jesus Christ our mediator with God; the fragmented man: the inner man and his awakening through solitude, renunciation and pureness of heart; the encounter with God and our response from faith, hope and mercy, the face of the «others»; God’s will in our life; prayer in Christian life whose pinnacle is contemplation, differentiating mental prayer and active contemplation from mystic or passive contemplation.